2017
DOI: 10.18865/ed.27.s1.295
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' Market Utilization among Supplemental Nutrition Assistance Program Recipients in New Orleans, Louisiana: Preliminary Findings

Abstract: <p class="Pa7"><strong>Objective: </strong>Farmers’ markets are increas­ingly being promoted as a means to provide fresh produce to poor and underserved communities. However, farmers’ market (FM) use remains low among low-income patrons. The purpose of our study was to examine FM awareness and use, grocery shopping behaviors, and internet use among Supplemental Nutrition Assistance Program (SNAP) recipients.</p><p class="Pa7"><strong>Design: </strong>A descriptive anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Nevertheless, more than a third of the customers at people-of-color-operated farmers markets are people of color. This finding is noteworthy as earlier studies have found that low numbers of people of color visit and shop at farmers markets (Nuss et al, 2017; Singleton et al, 2020; Skizim et al, 2017).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Nevertheless, more than a third of the customers at people-of-color-operated farmers markets are people of color. This finding is noteworthy as earlier studies have found that low numbers of people of color visit and shop at farmers markets (Nuss et al, 2017; Singleton et al, 2020; Skizim et al, 2017).…”
Section: Discussionsupporting
confidence: 58%
“…A study of 51 SNAP recipients in New Orleans found that only 47% of the study participants had ever been to a farmers market. The study found that 88% of the respondents shopped for fruits and vegetables at grocery stores and 84% obtained these items at Walmart ( Nuss et al, 2017 ). Skizim et al (2017) found that 63% of low-income New Orleans residents never visited a farmers market, while 27% of middle- and high-income residents never went to farmers market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An important aspect for future studies to consider studying is the impact of this program on SNAP participants' well-being. As has been seen in other studies [54], participants in our study who were not shopping at farmers' markets offering the incentive program had little awareness of the benefit [55].…”
Section: Discussionmentioning
confidence: 47%
“…Recommendations for Policy, Practice, and Research Previous studies have established evidence that SNAP recipients face various barriers (lack of transportation, lack of awareness, inconvenient time, location of operation, etc.) in their ability to access farmer's market incentive programs (Freedman et al, 2016;Nuss, Skizim, Afaneh, Miele, & Sothern, 2017;Olsho et al, 2015;Savoie-Roskos et al, 2016;). These potential limitations indicate that not all SNAP recipients may be able to make frequent FM trips that could in turn improve their access to healthier food options.…”
Section: Resultsmentioning
confidence: 99%